Q10 COENZYME FOR THE PROPHYLAXIS OF MIGRAINE IN CHILDREN AND ADOLESCENTS - Liana Tauberg (Amaltea Medical Publishing House, 2008)
The article presents the results of an open study of administration of a dietary supplement - coenzyme Q10, for the prophylaxis of migraine, on a group of 14 children aged between 10 an 14 years. A small dose, of only 60 mg daily, produced a more than 50% decrease of the number of days with headache, in 8 of the 14 children. The doses of NSAID taken by 9 of the 14 children were reduced by more than 50%. These results were obtained after only two months of supplementation. In previous adult studies, there have been noticed results after longer periods of supplementation, and with higher doses of coenzyme Q10 . There have been no adverse effects. This is a preliminary, open study, without placebo control, on a very small group of children. Coenzyme Q10 looks promising for migraine prophylaxis in children. But further, larger studies are needed to confirm its usefulness